Immigrants’ perception of business opportunities in Spain: the impact of general and specific human capital - Aliaga Isla, Rocío (Review of Business Management, 2014)
Perceiving business opportunities is an important part of entrepreneurship. This study analyzes how immigrants’ general and specific human capital influences their likelihood of perceiving business opportunities. Analysis focuses on comparison between a group of immigrants and a group of Spanish citizens. Data from the 2008 Global Entrepreneurship Monitor (GEM) was used. Logistic regression was used to analyze data. Results revealed that both immigrants’ and Spanish citizens’ human capital such as education is not significant to perceiving opportunities. Much to the contrary: the impact of specific human capital on perceiving opportunities is in general significant to both groups. This research reveals which specific types of human capital are relevant in the process of perceiving opportunities amongst immigrants. This paper is a novelty because it introduces a theoretical approach to the perception of opportunities within the universe of new businesses established by immigrants in Spain.